Information Literacy Based on Students Entrepreneurship at Sebelas Maret University Library - Haryanto Haryanto; Sapto Hermawan (Edumaspul: Jurnal Pendidikan, 2022)
Abstract The purpose of this study was to analyze the development of UNS Library UPT services through student entrepreneurship-based information literacy according to experts, librarians, library leaders, and students, as well as the obstacles faced in its implementation. The method used in this study is qualitative research with a descriptive approach and data analysis using Miles and Huberman. The data collection instruments used in this study were observation, interviews, documentation, and Focus Group Discussion (FGD). The results of the study, the development of entrepreneurship-based information literacy services for UPT Library UNS students was carried out through the empowerment of entrepreneurship collections, appointment of librarians in organizing entrepreneurial information literacy activities, the concept of implementing entrepreneurial information literacy was carried out in the form of seminars, workshops, FGDs in the field of entrepreneurship, as well as direct visits to various micro business unit business actors. Student entrepreneurship information literacy materials are in the form of training in animal husbandry, agriculture, digital business, and business products with small capital so that they can be duplicated and modified by students so that students can practice without difficulty in funding, besides that a motivator is also needed to foster enthusiasm in entrepreneurship among students. The obstacles faced by the UNS Library in implementing student entrepreneurship-based information literacy are the absence of librarians specializing in entrepreneurship to prepare planning for student entrepreneurial literacy activities and coordinators of entrepreneurial student groups at the UNS Library. Another obstacle is that no place in the UPT library can be used specifically for gathering entrepreneurial students to interact, discuss, grow ideas and develop businesses. Keywords: Information Literacy; Entrepreneurship; College Library; Student